Anatomy of the orexinergic, serotonergic, cholinergic and catecholaminergic systems in the brains of apes - Williams, Victoria Mary Elizabeth (My University, 2020)
Using immunohistochemistry, the nuclear parcellation of the cholinergic, catecholaminergic, serotonergic and orexinergic systems were described in two species of apes, the lar gibbon and common chimpanzee. The data obtained from this dissertation shows that these neuromodulatory systems are similar to that observed in a range of Eutherian mammals, including other primates, especially humans. Despite the similarities, unique features, in terms of neuronal morphology and distribution, were found within these neuromodulatory systems that might be Hominoid- or primate-specific, including: 1) a novel cluster of orexinergic neurons in the tuberal region of the hypothalamus, which to a certain extent, is also present in the human hypothalamus, revealing that it is most likely a shared feature of the Hominoidea; 2) an expansion of the lateral division of the serotonergic dorsal raphe nuclear complex was only observed in the common chimpanzee, and it is also present in humans; 3) the expansion of the cholinergic medullary tegmental field and cervical spinal cord, which are only present in the apes, including humans; 4) the soma forming the laterodorsal tegmental nucleus (LDT) were larger than the pedunculopontine (PPT) nucleus, which might be related to the size of the adult derivatives of the alar and basal plate; 5) the distribution of the catecholaminergic neurons forming the retrorubral nucleus (A8) was expanded in both apes, especially in the common chimpanzee, which is also present in humans, but not in other primate species; and 6) the presence of a compact division of the locus coeruleus (A6c), which has been found in other primates, but it is not present in other mammals, except for megachiropteran bats, and thus might be an important indicator of phylogenetic relationships. Given the consistency across mammals, including primates, it is advantageous to use animal models for the study of specific dysfunctions in these neuromodulatory systems in humans at a systems level
A thesis submitted to the School of Anatomical Sciences, Faculty of Health Sciences, University of the Witwatersrand in fulfilment of the requirements for the degree of Doctor of Philosophy